Patronase Dalam Rekrutmen Anggota Komisi Independen Pemilihan (KIP) Kabupaten Aceh Barat Daya Periode 2013-2018 - Leo Agustino; Sayed Fahrul (Universitas Sultan Ageng Tirtayasa, 2018)
Abstract: The recruitment of the member of Electoral Independent Commissionaire (KIP) of Aceh Barat Daya (Abdya) District from the period of 2013-2018 which is conducted by legislative (DPRK) Abdya shown the relation and interaction of power with the executive. One of the case is the dismissed of Muhammad Jakfar as the member of the Electoral Independent Commissionaire of the period 2013-2014 permanently in 2016 because of being involved the Aceh Party officials of the period 2011-2015. The election of Muhammad Jakfar at that time as the KIP’s member of the period 2013-2018 is interesting to study in the perspective of patronage. For that reason, the theory used in this study is theory of patronage. This research is used a qualitative descriptive approach method, which is construct the reality and process interactively. The findings of this research have shown the local head electoral (Pilkada) 2012 has drive the patronage in the recruitment of the member of KIP of Aceh Barat Daya district of the period of 2013-2018.Keywords: Aceh Barat daya (Abdya); Member of KIP; Patronage Abstrak: Rekrutmen anggota Komisi Independen Pemilihan (KIP) Kabupaten Aceh Barat Daya (Abdya) periode 2013-2018 yang dilaksanakan oleh Dewan Perwakilan Rakyat Kabupaten (DPRK) Abdya menunjukkan adanya relasi dan interaksi kekuasaan dengan lembaga eksekutif. Salah satunya adalah kasus pemberhentian Muhammad Jakfar oleh DKPP sebagai anggota KIP karena terlibat kepengurusan Partai Aceh Periode 2011-2015. Terpilihnya Muhammad Jakfar saat itu sebagai anggota KIP Aceh Barat Daya periode 2013-2018 menarik untuk dikaji dalam perspektif patronase. Teori yang digunakan dalam kajian ini adalah teori patronage. Kajian ini menggunakan metode pendekatan kualitatif deskriptif yaitu mengonstruksikan realitas dan proses secara interaktif. Dari hasil analisis, maka dapat dikatakan bahwa Pilkada Abdya tahun 2012 telah membuka ruang terjadinya patronase dalam rekrutmen anggota KIP Abdya periode 2013-2018.Kata kunci: Aceh Barat Daya (Abdya); Anggota KIP; Patronase.